A natural experiment of dietary overlap between introduced Rainbow Trout (Oncorhynchus mykiss) and native Puyen (Galaxias maculatus) in the Santa Cruz River, Patagonia - Tagliaferro, Marina Beatriz; Arismendi, Ivan; Lancelotti, Julio Lucio; Pascual, Miguel Alberto (Environmental Biology of Fishes)
Diet overlap between the native Puyen (Galaxias maculatus) and juvenile exotic Rainbow Trout (Oncorhynchus mykiss) was studied in 52 sites located along 306 km of the mainstem of the Santa Cruz River, one of the largest rivers in Patagonia. The relative abundance of both species varied along the river, with three clearly defined areas including an upstream “high Rainbow Trout to Puyen ratio” area (with abundances of 75 and 25 %, respectively), a midstream “intermediate Rainbow Trout to Puyen ratio” area (relative abundances between 75 and 25 %), and a downstream “low Rainbow Trout to Puyen ratio” area. The diet of the 2 species was analyzed across these 3 areas examining stomach content. Diet similarity between species was analyzed using a non-metric multidimensional scaling ordination technique; prey electivity was evaluated with the Ivlev’s Index; feeding tactics were studied by estimating prey-specific abundance. Both species showed a generalist feeding tactic, with Puyen exhibiting a more varied diet. Prey electivity was similar in both species, with the mayfly (Meridialaris chiloeensis), stoneflies (Klapopteryx kuscheli and Antarctoperla michaelseni), and the amphipod (Hyalella sp.) being the most frequently consumed prey. A significant diet overlap was found only in the downstream areas where a higher proportion of native fish occurs. The low diet overlap in upstream locations might be because of the high density of Rainbow Trout; while mid-stream could be due to the high secondary productivity spots. Our results suggest that the diet of native Puyen changed in relation to the abundances of Rainbow Trout in the stream. Fil: Tagliaferro, Marina Beatriz. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina. Universidad Nacional de Luján. Departamento de Ciencias Básicas; Argentina Fil: Arismendi, Ivan. State University of Oregon; Estados Unidos Fil: Lancelotti, Julio Lucio. Consejo Nacional de Investigaciones ...